Antibacterial activity of Thymus vulgaris essential oil alone and in combination with other essential oils - KATERYNA KON; MAHENDRA RAI (Nusantara Bioscience, 2012)
Abstract. Kon K, Rai M. 2012. Antibacterial activity of Thymus vulgaris essential oil alone and in combination with other essential oils. Nusantara Bioscience 4: 50-56. Essential oils (EOs) from plants represent an alternative approach in combating antibiotic-resistant bacteria. One of the EOs with proven antibacterial properties is Thymus vulgaris EO. The purpose of the present work was to investigate in vitro antibacterial activity of T. vulgaris EO alone and in combination with other EOs. The activity of T. vulgaris EO was screened in combination with 34 EOs against Staphylococcus aureus and Escherichia coli by disk diffusion method; then the most effective combinations were evaluated by broth microdilution method. Against S. aureus the synergistic effect was found in combination of T. vulgaris and Cinnamomum zeylanicum EOs with fractional inhibitory concentration (FIC) index of 0.26; Juniperus communis and Picea abies EOs showed additive effect (FIC indexes were 0.74 and 0.78, respectively). Combination of T. vulgaris EO with Aniba rosaeodora and Melissa officinalis EOs demonstrated synergistic effect against E. coli (FIC indexes were 0.23 and 0.34, respectively); combination of T. vulgaris and Mentha piperita EOs was additive (FIC index 0.55). Therefore, combining T. vulgaris EO with other EOs has potential in further enhancing its antibacterial properties.